Expression levels of 10 candidate genes in lung tissue of vaccinated and TB‐infected cynomolgus macaques. Issue 3 (16th February 2013) - Roodgar, Morteza; Lackner, Andrew; Kaushal, Deepak; Sankaran, Sumathi; Dandekar, Satya; Satkoski Trask, Jessica; Drake, Christiana; Smith, David Glenn
Abstract The expression of ten tuberculosis candidate genes in lung and lymph nodes of cynomologus macaques vaccinated and experimentally infected with Mycobacterium tuberculosis (Mtb) was quantified. The expression of TNFα, IL10, IL1β, TLR4, IL17, IL6, IL12, and iNOS in the lungs of vaccinated animals was higher than that of non‐vaccinated animals.